PENGUNGKAPAN BUKTI ADANYA PERBUATAN PIDANA DENGAN MENGGUNAKAN IDENTIFIKASI SIDIK JARI DI POLRES KUTAI - Paulus Paulus (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
AbstractIn recent years this problem of improving the quality and quantity of crime in Indonesia, has been frequently discussed. Even to say that the development in quantity of crimes in Indonesia from year to year shows a figure tends to increase.          Police Kutai Barat as the responsible agency in the field of security and public order cities Kutai Barat, have tried as much as possible in various ways in tackling security and public order disturbances. One of the most important means for the reintroduction of a wanted criminal was fingerprinted.According to the Code of Criminal Law Article 1, paragraph 2, which referred to the investigation are:"Serangakain action investigator in the case and in the manner stipulated in this Law to search for and collect evidence, that the evidence can make the light on the crime that occurred in order to find the suspects".Because fingerprints play an important role in the investigation, the investigator should really have the patience, perseverance, skill and have sufficient knowledge, especially knowledge about the searches or processing traces of fingerprints at a crime scene in order to obtain good results.